(untitled) (Research, Society and Development, 2020)
The present descriptive study aims to carry out a bibliographic survey of the main studies about high-intensity interval training (HIIT) and oxidative stress, enabling the systematization of information about its main concepts. There are still many controversies about the two themes and the relationship between them. After selecting articles, categories were defined to describe the concepts that guide the themes presented, describing the main concepts of HIIT, free radicals, oxidative stress, reactive oxygen species, endogenous and exogenous antioxidant defense systems and the relationship between interval training and oxidative stress. Thus, HIIT can contribute in a dual way on the organism, and among its deleterious effects, increase of oxidative stress, decreased performance and fatigue stand out. However, some studies have demonstrated that the physiological adjustments of HIIT provide beneficial effects on health, especially on the oxidizing capacity, and further studies are needed to identify other intracellular events related to oxidative stress that HIIT may cause.